Perceived work changes between 1981 and 1992 among aging workers in Finland - Nygård, Clas-Håkan; Huuhtanen, P.; Tuomi, Kaija; Martikainen, Rami (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVE ': 'Perceived changes in mental and physical work demands and work content were evaluated longitudinally.' ' METHODS ': 'Municipal workers (N=924) in the same job from 1981 (mean age 47 years) to 1992 (mean age 58 years) in the work content groups of mental, mixed mental and physical, or physical work responded to a questionnaire in both 1981 and 1992.' ' RESULTS ': 'The workers reported that the physical and mental demands of their jobs had mainly increased from 1981 to 1992, especially muscular work and use of knowledge. In 1992 the women still perceived higher physical demands than the men but felt they had greater possibilities to develop. The use of knowledge had increased, especially among the women, and was on the same level for both genders. The perception of changes differed in the 3 work content groups.' ' CONCLUSION ': 'Perceived work demands increase with age. Although the 3 work content categories differ somewhat as to perceived changes over time, in general, the changes may be more connected to personal factors than work factors. Older persons seem to work at a relatively higher capacity than younger workers, and this higher work load may be a risk factor for early work disability. Work demands and stress factors should therefore be surveyed and balanced according to the capacity of the aging worker. On the other hand, workers' perception of possibilities to develop seem to increase with age. The differences between men and women may especially diminish at a later age.
Keywords: age; inquiry; job change; longitudinal study; work demand